P104 Results of the first analysis of national lung cancer audit data based on cancer registration data. (15th November 2016) - Beckett, P; Khakwani, A; Hubbard, R; Vernon, S; Jack, R; Wood, N; Plewa, B; McAndrew, N; Dickinson, R; Navani, N; Harden, S; Woolhouse, I
Abstract : Introduction: The National Lung Cancer Audit (NLCA) has collected data for over 10 years, but in early 2015 a transition to using the Cancer Outcomes and Services Dataset (COSD) and cancer registration was begun and has now entirely superseded the legacy LUCADA dataset. An online portal (CancerStats) has been developed with a bespoke section providing near real time analysis of unprocessed COSD data for the NLCA. This portal currently focusses on data completeness, with plans to add process and treatment data in the near future. We report the results of the first 12 months of data collection using the new system (2015), and have compared this to the last year of LUCADA submissions (2014). Methods: The COSD was submitted monthly by English trusts on patients diagnosed with invasive lung cancer throughout 2015. This raw data was used to populate the data completeness tables on the CancerStats portal. An algorithm was developed to allocate a "trust first seen" to each patient record. Our presentation will include data from the final processed cancer registration records that have been validated using all available data sources within the National Cancer Registration Service (NCRAS). Welsh data submitted via their CANISC system will be available for our presentation. Results: 35, 000 individual cases of invasive lung cancer were submitted by English Trusts. Data completeness results are shown in Table 1 . Our final presentation will be updated with data from the processed cancer registration records that have been validated using all available data sources within the National Cancer Registration Service (NCRAS), as well as results from Welsh trusts. Conclusion: COSD submissions appear to capture more cases of lung cancer than LUCADA. During this transition period, the quality of the data was less good than previous years with significant variation across organisations. However, data completeness for stage and treatment is expected to be better than indicated since final registered cases use data from a variety of other sources. CancerStats offers the opportunity for teams to monitor their data quality and to iteratively improve their internal processes to deliver robust data for future years, in particular patient factors such as performance status which is not available elsewhere.